Transcranial Magnetic Stimulation in the Diagnosis of Cervical Compressive Myelopathy: Comparison With Spinal Cord Evoked Potentials. Issue 3 (1st February 2015) - Funaba, Masahiro; Kanchiku, Tsukasa; Imajo, Yasuaki; Suzuki, Hidenori; Yoshida, Yuichiro; Nishida, Norihiro; Taguchi, Toshihiko
Abstract : Study Design: Single-center retrospective study. Objective: To reveal the characteristic changes in central motor conduction time (CMCT) produced by transcranial magnetic stimulation among the responsible levels of cervical compressive myelopathy (CCM). Summary of Background Data: CMCT is a useful and noninvasive measure for evaluating the central motor pathway. However, a systematic correlation between CMCT findings and the responsible level of CCM has so far not been addressed in a large patient cohort. Method: We measured CMCT in 75 patients with CCM who were determined by intraoperative spinal cord evoked potentials to have a single site of conduction abnormality at the intervertebral level. Twenty-one healthy controls were also evaluated. Motor evoked potentials, compound muscle action potentials, and F wave were recorded from bilateral abductor digiti minimi (ADM) and abductor hallucis (AH) muscles. CMCT was calculated as follows: motor evoked potentials latency − (CMAPs latency + F latency − 1)/2 (ms). Result: The mean values of ADM-CMCT and AH-CMCT at each responsible level were significantly longer than those of normal values ( P < 0.01). However, the mean value of ADM-CMCT at the C6–C7 level was markedly shorter than those at the other levels, whereas the mean values of AH-CMCT were not significantly different between each responsible level. We determined that an ADM-CMCT longer than 7.9 ms (mean + 2.5 standard deviation) was abnormal. Using this definition, the sensitivity of ADM-CMCT for CCM was 92% for C3–C4 myelopathy, 95% for C4–C5, 58% for C5–C6, and 9% for C6–C7. Conclusion: ADM-CMCT is useful for the screening of CCM rostral to the C5–C6 level. Diagnosis of patients with C6–C7 myelopathy should include assessment of the AH-CMCT. Level of Evidence: 4 Abstract : The sensitivity of abductor digiti minimi-central motor conduction time for cervical compressive myelopathy was 92% for C3–C4 myelopathy, 95% for C4–C5, 58% for C5–C6, and 9% for C6–C7. Abductor digiti minimi-central motor conduction time is useful for screening of cervical compressive myelopathy rostral to the C5–C6 level. Diagnosis of patients with C6–C7 myelopathy should include assessment of the abductor hallucis-central motor conduction time.